Modulation of Social Cognition via Hallucinogens and “Entactogens” - Preller, Katrin H.; Vollenweider, Franz X. (Frontiers in Psychiatry, 2019)
Social cognition is a fundamental ability in human everyday lives. Deficits in social functioning also represent a core aspect of many psychiatric disorders. Yet, despite its significance, deficits in social cognition skills are insufficiently targeted by current treatments. Hallucinogens and entactogens have been shown to have the potential to modulate social processing. This article reviews the literature on the influence of hallucinogens and entactogens on social processing in controlled experimental studies in humans and elucidates the underlying neurobiological and neuropharmacological mechanisms. Furthermore, it identifies current knowledge gaps and derives implications for hallucinogen-assisted treatment approaches as well as the development of novel medication for trans-diagnostic impairments in social cognition.